Investigation of Contamination of Community Groundwater Sources with Antibiotics in Informal Settlements of Kisumu, Kenya - Karimi, Kellen Joyce (University of the Witwatersrand, Johannesburg, 2023)
Antibiotics have been used to cure diseases, but there are growing concerns about the risk to human health caused by inadvertent exposure to low levels of antibiotics in the environment. Despite extensive reporting from the developed world on antibiotic pollution of groundwater, relatively little study has been conducted on antibiotic contamination of groundwater in the developing countries, particularly informal settlements. Antibiotic usage and misuse have long been seen as clinical events, with little understanding of the role of disposal in the development of environmentally induced resistance. Exposure pathways that contribute to groundwater contamination in informal settlements put residents at odds because they already face inequalities, such as a high disease burden exacerbated by antibiotic resistance; thus, proper antibiotic disposal is critical in protecting human and environmental health. The purpose of this cross-sectional study was to establish the prevalence of groundwater contamination with the common antibiotics’ such as sulfamethoxazole, trimethoprim, and metronidazole, and the related antibiotic resistance and the human health risk of exposure. Ethical clearance to conduct research was obtained from three institutions as follows: - the Health Research Ethic Committee of the university of the Witwatersrand (HREC. Protocol Number M190412); the Kenyatta National Hospital and University of Nairobi Ethics and Research Committee (KNH/UoN-ERC. Ref No. P71910/2018); and the National Commission for Science, Technology, and Innovation (Ref No. NACOSTI/P/19/3232/28732). Each respondent gave informed consent to participate in the study. Anonymity was maintained at all levels of the study to protect the study participants from identification. Antibiotic use, which is connected to antibiotic disposal, was evaluated in a random sample of 447 families. From the 188 mapped groundwater sources, a random sample of 49 groundwater sources was chosen, and water samples were taken for antibiotic concentration analysis utilising a solid-phase extraction and liquid chromatography coupled to magnetic sector high resolution mass spectrometry (SPE-LC-MS/MS). The Kirky-Bauber diffusion method was used to test antibiotic resistance in Escherichia coli. The community's potential groundwater contamination routes were assessed by determining antibiotic use and disposal among households as well as assessing the environmental risk of exposure. In the households visited, 75% (n=337) were female and 25% (n=110) were male. The prevalence of antibiotic use in informal settlements was 43% (n=193), with 70% (n=137) users reporting that they obtained the antibiotics through a prescription from a health practitioner. A significant relationship was observed between having HIV/AIDS and acquiring antibiotics through a prescription; p=0.001. An association was also observed among the informal settlements, where a lower number of MNY B dwellers did not receive a prescription for the antibiotics acquired. There was no statistically significant difference in antibiotic use between males and females; odds ratio=1.33; whereas there was a difference in HIV/AIDS status; odds ratio=0.313; and among informal settlements where the odds of using antibiotics were reduced in NY B; odds ratio=0.42. Respondents who used antibiotics either kept the unused antibiotics for future use 87.1% (n=27) or disposed them. Among the disposals 51.6% (n=16) disposed in pit latrines, 16.1% (n=5) dispose in compost pits, and 6.5% (n=2) dispose the remaining antibiotics by burning. Females completed their antibiotic doses at a higher rate (36.3%; n=117) than males (32.5%; n=39). Significant difference was observed in completion rate among the HIV/AIDS positive and negative respondents as well as among informal settlements; p<0.000 and p=0.001 respectively. On the other hand, groundwater use in these communities is widespread. Respondents used it for a variety of purposes, including drinking (9%; n=39), though they declined to report. Awareness of the health consequences of drinking antibiotic-contaminated water was also low (35%; n=158), especially among households that reported antibiotic use; p=0.003. Only Sulfamethoxazole was detected in 7 out of 49 groundwater samples at a detection frequency of 14.3%; with concentrations ranging from nd to 258 ng/L. Escherichia coli and Cryptosporidium parvum were isolated from all the 49 water samples and E. coli isolates from 3 (6%) water samples were resistant to sulfamethoxazole with Inhibition Zone Diameters of 0.8 mm, 10.5 mm, and 11.5 mm. The 3 water samples were however not among samples where sulfamethoxazole was detected. The Hazard Quotient was 0 (zero), and therefore no risk of exposure to sulfamethoxazole in the environment, but the level of antibiotics that trigger antibiotic resistance is not known. Because of the rising problem of antibiotic resistance due to overuse and incorrect disposal, teaching on safe antibiotic prescription should be incorporated into medical training for all cadres. In addition to educating patients on proper use and disposal, the ministries of health should ensure the antimicrobial stewardship standards are adhered to both locally and worldwide. Follow-up research of antibiotic resistance discovered in three groundwater sources must be done to eliminate the possible sources and prevent further spread. This study is instrumental in informing the inclusion of antibiotics on the list of frequently monitored contaminants during water treatment, as well as serving as a starting point for antibiotic surveillance in Kenya.
A thesis submitted in fulfilment of the requirements for the Degree of Doctor of Philosophy, to the Faculty of Health Science, School of Pathology, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Contamination; Community; Groundwater; Antibiotics; Informal Settlements; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education